An Overview of the driving forces behind energy demand in China's construction industry: Evidence from 1990 to 2012. (June 2017) - Hong, Jingke; Li, Clyde Zhengdao; Shen, Qiping; Xue, Fan; Sun, Bingxia; Zheng, Wei
Abstract: The rapid urbanization in China has produced a large demand for energy in the past decades. It is therefore urgent to have an understanding of the driving forces behind the energy increase in the construction industry. This study applies structural decomposition analysis (SDA) to quantify the effects of driving factors from insight into consumption and production. The results show that the energy consumption trajectory of China's construction industry is the result of competition between the effect of increasing final demand and improvement in energy efficiency. Although the effect of consistent efforts in structure optimization by the central government was significant from 2007 to 2012, the potential to save much energy still lies in structure optimization in energy, production, and final demand. According to the projection, structural upgrades in economy would be the most important factor for energy reduction in 2020. Scenario analysis further indicated that the percentage change of energy increments in 2020 can be reduced at 22% of 2010 level under the optimistic scenario. Sector aggregation analysis revealed that more aggregates would increase uncertainty to some extent and result in a misinterpretation of the importance of the underlying factors. According to the quantitative analysis in this study, the percentage change of total embodied energy consumption in the construction industry should be limited below 25% of 2010 level at the end of the 13th Five-Year Plan.